2010
DOI: 10.1016/j.ejvs.2009.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Access for Filter-protected Carotid Artery Stenting: A Useful Tool to Reduce Cerebral Embolisation

Abstract: Transcervical filter-protected CAS, compared with classic percutaneous procedures, seems to reduce clinical events and DW-MRI ischaemic damage and may be useful in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 25 publications
1
49
1
Order By: Relevance
“…In main group coronary complications that were causes of death were in 1.0%. It is not a bad index because some authors observed postoperative cardiac complications in 47-58% patients (Ignatev et al, 2011;Serajitdiniov, Vladimirsky and Lifentsov, 2011;Palomboa et al, 2010). Amputations of lower extremities in control group were made in 2.8%, and in main group -in 2.0% patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In main group coronary complications that were causes of death were in 1.0%. It is not a bad index because some authors observed postoperative cardiac complications in 47-58% patients (Ignatev et al, 2011;Serajitdiniov, Vladimirsky and Lifentsov, 2011;Palomboa et al, 2010). Amputations of lower extremities in control group were made in 2.8%, and in main group -in 2.0% patients.…”
Section: Discussionmentioning
confidence: 99%
“…In control group they were 8.5%, in main group -4.0%. Based on literature data a number of postoperative complications reaches 12-33.3%, and 10-29.2% cases (Shaarafeev, Аkberov and Кorobov, 2009;Palomboa et al, 2010) required additional reconstructive operations in the nearest postoperative period. Lethality accounted for 8.5% in control group, and 2.0% -in main group.…”
Section: Discussionmentioning
confidence: 99%
“…14) In other studies, comparing transcervical and transfemoral CAS, no contralateral hemispheric infarcts on DWI-MRI were found in the transcervical CAS group, unlike in the transfemoral CAS group. 15,16) However, transcervical CAS may cause major complications because CCA is close to significant anatomical structures. 14) Thus, transcervical CAS is more invasive than transfemoral, transbrachial, or transradial access.…”
Section: Discussionmentioning
confidence: 99%
“…Even in such case, the data must be interpreted in the light of the wide use of the transcervical approach that certainly concurs to decrease the embolic load and, therefore, the onset of new cerebral DW-MR lesions 32 .…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…undergoing respectively CEA or BMT, reported a better complication rate after carotid surgery (2% vs 16%) [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] .…”
Section: Accepted Manuscriptmentioning
confidence: 99%